Evaluasi Sistem Informasi Rekam Medis Di RSUD Kota Surakarta Dalam Mendukung Rekam Kesehatan Elektronik - Sri Wahyuningsih Nugraheni - APIKES Citra Medika Surakarta (Indonesian Journal on Medical Science, 2017)
Abstract: Management of medical records in RSUD Kota Surakarta currently supported by the SIM RS Pilar Hospital. Coordination between the relevant sections of data becomes easier. Part associated with the patient's medical record data includes registration, inpatient, outpatient, emergency, laboratory, radiology, pharmacy and cashier.SIM RS Pilar Hospital became a strength in support of an electronic medical record (RKE), but not every use of computer applications in service medically known as the RKE. This study is a qualitative research case study to evaluate the management of medical records in hospitals Surakarta using an evaluation model Health Metrics Network (HMN). The results of the evaluation of the management of medical records in RSUD Kota Surakarta in terms of input that is already inadequate resources, data sources has also been adequate, but the indicators SIM RS Pilar Hospital is not yet fully known as RKE. Evaluation in terms of the process include data management, coordination and leadership is adequate. Evaluation in terms of output includes product information, dissemination and utilization of information is adequate. Based on an evaluation in terms of input, process and output, it can be given suggestions for SIM RS Pilar Hospital support RKE is bridging withDitjen Dukcapil Kemendagri, data entered and reports issued by the system can be multimedia and system capable of displaying direct reports internally and externally without processing with Microsoft Excel.Keyword :medical record, information system, electronic, hospital Â Abstrak: Pengelolaan rekam medis di RSUD Kota Surakarta saat ini didukung dengan adanya SIM RS Pilar Hospital.Koordinasi data antar bagian terkait menjadi semakin mudah. Bagian terkait dengan data rekam medis pasien meliputi pendaftaran, rawat inap, rawat jalan, gawat darurat, laboratorium, radiologi, farmasi dan kasir.SIM RS Pilar Hospital menjadi kekuatan dalam mendukung Rekam Kesehatan Elektronik (RKE), namun tidak setiap penggunaan aplikasi komputer dalam pelayanan kesehatan disebut sebagai RKE. Penelitian ini adalah jenis penelitian kualitatif study kasus untuk mengevaluasi pengelolaan rekam medis di RSUD Kota Surakarta menggunakan model evaluasi Health Metric Network (HMN). Hasil evaluasi pengelolaan rekam medis di RSUD Kota Surakarta dari segi input yaitu sumber daya sudah memadai, sumber data juga sudah memadai, namun indikator SIM RS Pilar Hospital belum sepenuhnya disebut sebagai RKE. Evaluasi dari segi proses meliputi manajemen data, koordinasi dan kepemimpinan sudah memadai. Evaluasi dari segi output meliputi produk informasi, diseminasi dan pemanfaatan informasi sudah memadai. Berdasarkan evaluasi dari segi input, proses dan output, maka dapat diberikan saran agar SIM RS Pilar Hospital mendukung RKE yaitu bridging dengan Ditjen Dukcapil Kemendagri, data yang dimasukkan dan laporan yang dikeluarkan sistem dapat bersifat multimedia serta mampu menampilkan secara langsung laporan intern dan ekstern tanpa melakukan pengolahan dengan Microsoft Excel. Kata kunci:rekam medis, sistem informasi, elektronik, rumah sakit